Influence of Boronizing Treatment and Parameters of Erosion Test on Sand Slurry Erosion of X52 Steel - Dakmoussi Maamar; Sami, Zidelmel; Allaoui Omar (Metallurgical and Materials Engineering, 2024)
Slurry erosion is one of the main problems associated with pipeline transportation of gas and oil. The impact of slurry concentration and velocity on slurry erosion resistance before and after boronizing API X52 steel was investigated in this study. Two slurry velocities of 4 and 6 m/s, and slurry concentrations of 400, 600, and 800 g/l were employed. Boronizing was performed at 900 °C for 4 h in a powder mixture containing 5% B4C as the boron source, 5% NaBF4 as the activator, and 90% SiC as the diluent. It was found that when the slurry concentration and velocity rise, so does the erosion rate, or weight loss. In comparison with the unboronized X52 steel, the results demonstrated that the formation of boride layers significantly improved the surface hardness and slurry erosion resistance.